2020
DOI: 10.1097/njh.0000000000000697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perceptions of Spiritual Care Among Patients With Life-Threatening Cancer, Primary Family Caregivers, and Hospice/Palliative Care Nurses in South Korea

Abstract: This study aimed to compare perceptions of spiritual care among patients with life-threatening cancer, their primary family caregivers, and hospice/palliative care nurses. Data were collected using both structured and unstructured approaches. Structured questionnaire data were examined using statistical analysis methods, and unstructured data were examined using content analysis to compare the 3 participant groups. The questionnaire revealed that among all 3 groups, spiritual care was commonly percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Spirituality has been seen to bring positive outcomes in extremely stressful situations such as life-threatening cancer or hospice care. 34,35 The tremendous fear which prevailed at the beginning of the COVID-19 outbreak, could bring more significant consequences than a typical, stressful situation. More intense, stressful situations may require a spiritual approach that goes beyond optimism and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality has been seen to bring positive outcomes in extremely stressful situations such as life-threatening cancer or hospice care. 34,35 The tremendous fear which prevailed at the beginning of the COVID-19 outbreak, could bring more significant consequences than a typical, stressful situation. More intense, stressful situations may require a spiritual approach that goes beyond optimism and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported that clinicians expressed sensitivity to cancer patients. [2,4,6,11] Clinicians recognized the importance and value of appropriately timed conversations about spirituality with the patients. Also, with the interprofessional approach it said that it is a key assessment to know when it is needed to refer patients to chaplains and other people skilled in providing spiritual care.…”
Section: Theme 2: Clinician's Sensitivity To Cancer Patientsmentioning
confidence: 99%
“…The clinicians' perception of spirituality is one of the essential aspects to assess, as these would be beneficial in providing oncologic care to the patients. Multiple studies have been conducted on patients' views towards spirituality and less on the views of the health care providers, mainly qualitative studies [11]. Thus, a need to further study and explore this subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, patients have to bear physical, economic, and psycho-social challenges. These challenges generate holistic physical-psychological-social-spiritual pain (Kang and Kim, 2020). Moreover, these challenges present different degrees of spiritual care needs (O'Brien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%